Annual Plan 1971-72 Part-II Government of Tripura - Planning Commission (Planning Commission, 1971)
Summary Statement-Outlay and Expenditure Annual Plan Plan Outlay - Schemewise Annual Plan Statement Physical Programmes.
Government of Tripura